Analgesic Effectiveness Study Of N-4t-Butylbenzoyl Acetate Compound In Male Balb-C Strain Mice - Hadi Barru Hakam Fajar Siddiq; Rosida Rosida; Dewi Riskha Nurmalasari; Resa Try Afriani; Yuriko Titan Yanindra (LPPM Akafarma Sunan Giri Ponorogo, 2025)
This study aims to understand the activity and effective dose of N-4t-butylbenzoyl Acetate compound as a pain reliever. The analgesic activity test conducted was divided into 5 treatment groups. The analgesic effect test was performed using male mice from the Balb-C strain. In each test, each group consisted of 5 experimental animals. The first group (negative control) was given 1% Na-CMC suspension; the second group (positive control) received 400 mg/kgBW ibuprofen; while the third, fourth, and fifth groups were successively given 200, 400, and 600 mg/kgBW of N-4t-butylbenzoyl Acetate compound, respectively. After the treatment was given to each test animal, an analgesic test was conducted with a 30-minute interval. After that, it was injected with 1% acetic acid and observed for 180 minutes; every 10 minutes, the movement was observed for all treatments. The analysis was carried out by comparing the number of movements (writing reflex). Data analysis was performed statistically using ANOVA (analysis of variance). The number of mouse activities produced by male mice of the Balb-C strain showed that the N-4t-butylbenzoyl acetate compound at a dose of 1.56 mg had the highest activity, % protection, and % analgesic effectiveness compared to the other two doses. Based on statistical analysis, there was no significant difference in all treatments of the N-4t-butylbenzoyl acetate compound when compared to ibuprofen (positive control)